Differential Expression of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) Open Reading Frame 5, but not Apoptogenic Cytokines, Contribute to Severe Respiratory Disease in Pigs Infected with Type 2 PRRSV Compared with Pigs Infected with Type 1 PRRSV. Issue 2 (February 2016) - Han, K.; Lee, J.; Park, C.; Choi, K.; Jeong, J.; Park, S.-J.; Kang, I.; Chae, C.
Summary: The aim of this study was to compare the expression of open reading frame 5 (ORF5) of porcine reproductive and respiratory syndrome virus (PRRSV) and apoptogenic cytokines in the lungs from pigs infected with type 1 and type 2 PRRSV. Microscopical lung lesion scores and the mean number of apoptotic cells were significantly ( P <0.05) higher in pigs with type 2 PRRSV infection than in those with type 1 PRRSV infection. The score for the mean number of PRRSV ORF5-positive cells per unit area of lung was significantly ( P <0.05) higher in pigs with type 2 PRRSV infection. There were no significant differences in the expression of tumour necrosis factor-α and interleukin-1 in lung tissues between type 1 and type 2 PRRSV-infected pigs. The severity of microscopical lung lesions and the number of apoptotic cells correlated well with the number of PRRSV ORF5-positive cells. Therefore, differential expression of PRRSV ORF5, but not apoptogenic cytokines, may attribute to the severity of lung lesions and apoptosis in lungs in PRRSV infection. These results suggest that expression of PRRSV ORF5 may be a critical determinant for different virulence between PRRSV genotypes in terms of respiratory disease.